INVESTMENT MANAGEMENT AGENCY AFTER THE ENACTMENT OF LAW NUMBER 1 OF 2025 AND ITS IMPLICATIONS FOR REGIONALLY-OWNED ENTERPRISES - Nugraha, Dwi Putra; Sigrid, Stephanie; Natasha, Livia Cheryl; The, Jennifer (Awang Long Law Review, 2025)
Article 1 point 23 of Law Number 1 of 2025 concerning the Third Amendment to Law Number 19 of 2003 concerning State-Owned Enterprises brings a new paradigm for the management of State-Owned Enterprises, especially related to the emergence of the Daya Anagata Nusantara Investment Management Agency as a strategic investment super holding company. The presence of this agency marks a fundamental transformation of State-Owned Enterprises, which has legal implications for the concept of separate state assets. However, this change has created a gap with Regionally-Owned Enterprises, which still operate under Government Regulation Number 54 of 2017 concerning Regionally-Owned Enterprises and face limitations in terms of capital, governance, and political intervention. This paper analyzes the relationship between the Investment Management Agency and Regionally Owned Enterprises in the context of decentralization, and explores the relevance and potential of establishing Investment Management Agencies at the regional level. The results of the study show that strengthening regional investment governance through the establishment of regional Investment Management Agencies has the potential to increase efficiency, transparency, and investment attractiveness, while promoting the harmonization of national and regional interests in sustainable development.